Increasing Clindamycin and Trimethoprim-Sulfamethoxazole Resistance in Pediatric Staphylococcus aureus Infections. (13th July 2018) - Khamash, Dina F; Voskertchian, Annie; Tamma, Pranita D; Akinboyo, Ibukunoluwa C; Carroll, Karen C; Milstone, Aaron M
Abstract: The epidemiology of Staphylococcus aureus infection in children is dynamic. We conducted a retrospective observational study on pediatric clinical cultures, performed between 2005 and 2017, that grew S aureus to determine temporal trends in antibiotic resistance. Although methicillin resistance declined, clindamycin and trimethoprim-sulfamethoxazole resistance increased significantly, especially among community-onset isolates.